Bewegung als Menschenrecht? - Messing, Sven; Krennerich, Michael; Abu-Omar, Karim; Ferschl, Susanne; Gelius, Peter (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung, 2022)
Einleitung Durch den Lockdown und die Ausgangsbeschr.nkungen w.hrend der COVID-19 Pandemie hat sich der Stellenwert von Bewegung in der .ffentlichen Wahrnehmung verändert. Während in Spanien Sport im Freien für 48 Tage verboten war, galt Bewegung an der frischen Luft beispielsweise in Bayern als triftiger Grund, die eigene Wohnung oder das eigene Haus zu verlassen. Aus diesem Grund stellt sich nun vermehrt die Frage: Haben Menschen ein Recht auf Bewegung? Methode Der Beitrag diskutiert die Fragen, ob es ein Menschenrecht auf Bewegung gibt, wie sich ein solches Recht konkretisieren l.sst und inwieweit aus dem Recht staatliche Verpflichtungen im Bereich Bewegung abgeleitet werden k.nnen. Hierfür werden menschenrechtliche Konzepte auf ein m.gliches Recht auf Bewegung angewendet und der Mehrwert eines Rechts auf Bewegung diskutiert. Ergebnisse Ein Recht auf Bewegung kann aus etablierten Menschenrechten wie dem Recht auf Gesundheit, dem Recht auf Erholung und Freizeit, dem Recht auf Bildung und dem Prinzip der Nichtdiskriminierung abgeleitet werden. Jedes dieser Rechte hat einen Bezug zu wichtigen Aspekten von Bewegung wie dem gesundheitlichen Nutzen oder der Bedeutung körperlicher Aktivität für die psychologische und emotionale Entwicklung von Kindern und Jugendlichen. Wenn Bewegung als Menschenrecht definiert wird, kann dieses Recht anhand der Kategorien Verfügbarkeit (availability), offener Zugang (accessibility), Annehmbarkeit (acceptability) und Qualit.t (quality) konkretisiert werden. Außerdem wären Staaten dazu verpflichtet, dieses Recht zu respektieren, zu schützen und zu gewährleisten. Diskussion Die Anerkennung eines eigenst.ndigen Rechts auf Bewegung h.tte den Vorteil, dass der multidimensionale Charakter von Bewegung besser abgebildet werden k.nnte als wenn Bewegung lediglich als Element des Rechts auf Gesundheit konzeptualisiert wird. Doch die COVID-19 Pandemie zeigt auch, dass sich gegens.tzliche Verpflichtungen sogar aus dem gleichen Menschenrecht ableiten lassen: Während Bewegung grundsätzlich sehr relevant für die Prävention nichtübertragbarer Erkrankungen ist, erforderte die Pandemie auch, die Mobilität der Bevölkerung aus Gründen des Gesundheitsschutzes zu reduzieren. In solchen Fällen muss eine angemessene Abwägung der betroffenen Rechte durch den Staat erfolge
Keywords: Bewegung; Sport; Menschenrecht

Capital4Health: Opportunities for active Lifestyles: A Research Network for interactive Knowledge Exchange in Health Promotion - Gelius, Peter; Till, Maike; Ferschl, Susanne; Abu-Omar, Karim; Pfeifer, Klaus (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Development of national physical activity recommendations in 18 EU member states: A comparison of methodologies and the use of evidence - Tcymbal, Antonina; Gelius, Peter; Abu-Omar, Karim; Foster, Charlie; Whiting, Stephen; Mendes, Romeu; Titze, Sylvia; Dorner, Thomas Ernst; Halbwachs, Christian; Duclos, Martine; Toussaint, Jean Francois; Wendel-Vos, Wanda; et al. (BMJ Open, 2021)
Objectives The aim of the study is to compare how member states of the European Union (EU) develop their national physical activity (PA) recommendations and to provide an overview of the methodologies they apply in doing so. Information was collected directly from the physical activity focal points of EU member states in 2018. Five countries were chosen for detailed case study analysis of development processes. Design Cross-sectional survey. Participants The representatives of the 28 EU member state governments to the EU physical activity Focal Point Network. Outcome measures From national documents we extracted data on (1) the participants of the development process, (2) the different methods used during development, and (3) on which sources national PA recommendations were based. An additional survey for case study countries provided details on (1) anonymised information on the participants of development process, (2) methods employed and rationale for choosing them, (3) development process and timeline, and (4) main source documents used for recommendation development. Results Eighteen national documents on PA recommendations contained information about development process. The results showed that countries used different approaches to develop national recommendations. The main strategies were (1) adoption of WHO 2010 recommendations or (2) a combination of analysis and adoption of other national and international recommendations and literature review. All of the five case study countries relied on review processes rather than directly adopting WHO recommendations. Conclusions While there are arguments for the use of particular strategies for PA recommendation development, there is currently no evidence for the general superiority of a specific approach. Instead, our findings highlight the broad spectrum of potential development methods, resources utilisation and final recommendations design currently available to national governments. These results may be a source of inspiration for other countries currently planning the development or update of national PA recommendations.
CRIS-Team Scopus Importer:2021-04-30
Keywords: health policy; protocols & guidelines; public health

Exploring the links between Energy drink use, poverty related factors and health risk behaviour among Young Swiss adults - Lehmann, Susanne; Abel, Thomas (Postersession at Nationale Tagung für Gesundheit und Armut, 2016)

Fit und gesund in der Pflege?! Ergebnisse aus dem Forschungsverband Capital4Health. - Lehmann, Susanne; Till, Maike; Chioran, Raluca-Mariana; Gelius, Peter; Abu-Omar, Karim; Grüne, Eva; Popp, Johanna; Carl, Johannes; Pfeifer, Klaus (Postersession at Fortbildung der Geschäftstellenleiter der Gesundheitsregionen+. Landshut, 2019., 2019)

[Health Status of Young Men in Switzerland: Monitoring Results from Conscription]. - Staub, Kaspar; Wyss, Thomas; Lehmann, Susanne; Abel, Thomas; Rühli, Frank (Praxis, 2015)
Due to their representativeness and consistent measurement standards the medical und sports data of the Swiss conscripts provide a valuable basis for a continuous health monitoring of young Swiss men. During three to four years, the prevalence of overweight and obesity seems to stabilise on a high level. After a longer period of decreasing performance at the endurance test between the 1980s and 2002, the level of physical performance in the fitness test does no longer decrease since 2006. However, health and health behaviour show significant regional and socioeconomic inequalities among young Swiss men. Besides economic resources and education, major driving factors behind these inequalities can be identified in health knowledge, values, and attitudes.

Kooperative Planung: Grundlagen, theoretische Einordnung und Anwendungsfelder in der Sportwissenschaft. - Gelius, Peter; Sommer, Raluca; Ferschl, Susanne; Till, Maike; Frahsa, Annika; Abu-Omar, Karim (24. dvs-Hochschultag „Sport im öffentlichen Raum“, 2019)

Kulturkapital und Gesundheitskompetenz junger Erwachsener. - Lehmann, Susanne; Abel, Thomas („Daten gewinnen, Wissen nutzen für die Praxis von Prävention und Versorgung“ 51. Wissenschaftliche Jahrestagung der Deutschen Gesellschaft für Sozialmedizin und Prävention (DGSMP) – 30. Wissenschaftliche Jahrestagung der Deutschen Gesellschaft für Medizinische Soziologie (DGMS) – 6. LGL Kongress für den Öffentlichen Gesundheitsdienst (ÖGD) in Zusammenarbeit mit dem Medizinischen Dienst der Krankenversicherungen in Bayern (MDK), 2015)

Measuring capabilities in health and physical activity promotion: a systematic review. - Till, Maike; Abu-Omar, Karim; Ferschl, Susanne; Reimers, Anne Kerstin; Gelius, Peter (BMC Public Health, 2021)
Background: The capability approach by Amartya Sen and Martha Nussbaum has gained increasing attention in the field of public health. As it combines individual, social and structural factors and shifts the focus of attention from the actual behavior towards available options for health behaviors that people can actually choose from, it may help advance our understanding of complex health issues. Objectives: The aim of this article is to identify and describe tools available to measure capabilities within the context of health, with a specific focus on capabilities for health-enhancing physical activity. Method: We conducted a systematic literature review using 11 databases covering scientific journal articles published in English or German between the years 2000 and 2019 with a focus on capabilities for health or physical activity. Results: We found a total of 44 articles meeting our inclusion criteria. Four articles measured capabilities using qualitative methods, one combined qualitative and quantitative methods, while the rest used quantitative methods. We identified a total 11 different capability questionnaires, all showing moderate to good validity/reliability. Only one questionnaire and one interview-based tool specifically dealt with capabilities for health enhancing physical activity. Conclusion: Although we were able to identify measurement tools for capabilities in health, this review has shown that there is no generic tool available for the measurement across all population- and age-groups, and tools focusing on physical activity are scarce. However, our results can be used as guide for future projects that aim at measuring capabilitie
Keywords: Capability Approach; Public Health; Measurement; Operationalization; Physical activity; Health Outcomes; Questionnaires

P08-11 Capabilities and capitals for leisure-time physical activity among young adults: findings from Switzerland - Ferschl, Susanne; Gelius, Peter; Abu-Omar, Karim; Abel, Thomas (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
CRIS-Team WoS Importer:2022-09-23

Physical Activity as a Human Right? - Messing, Sven; Krennerich, Michael; Abu-Omar, Karim; Ferschl, Susanne; Gelius, Peter (Health and Human Rights, 2021)
Public awareness of the importance of physical activity has increased due to the many lockdowns imposed during the COVID-19 pandemic. This has brought more widespread attention to a question previously confined primarily to parts of the physical activity promotion community: Do humans have a right to be active? While the public health benefits of physical activity are undisputed, up to now no clear understanding has emerged as to whether physical activity represents a human right. Even though the right to physical activity is not explicitly recognized in international human rights treaties, it seems possible to derive it from well-established human rights such as the right to health, the right to rest and leisure, the right to education, and the principle of nondiscrimination. This paper shows how a right to physical activity could be derived from international human rights treaties, how the attributes of such a right could be defined, and which state obligations would be associated with it. Given that the current human rights discourse in this field focuses mainly on the interconnections between sport and human rights, we would like to argue that there is added value in a debate about physical activity as a human right.<br
Keywords: physical activity; human right; public health

S11 Improving knowledge co-creation and participation in physical activity promotion: The cooperative planning approach - Gelius, Peter; Sommer, Raluca; Ferschl, Susanne; Till, Maike; Abu-Omar, Karim; Semrau, Jana; Helsper, Natalie; Kohler, Simone; Dippon, Lea; Pfeifer, Klaus; Rütten, Alfred; Popp, Johanna; et al. (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
CRIS-Team WoS Importer:2022-09-23

Scaling-up auch in der Bewegungsförderung? - Ferschl, Susanne; Allmeta, Anila; Fleuren, Tobias; Weege, Mayra Heloise; Abu-Omar, Karim; Gelius, Peter (Bewegungstherapie und Gesundheitssport, 2020)
Die flächendeckende Verbreitung erfolgreicher Interventionen der Gesundheitsförderung ist eine wichtige Voraussetzung, um messbare und nachhaltige Gesundheitswirkungen auf Bevölkerungsebene zu erzielen. Das Konzept des Scaling-Up bietet Ansätze, um Pilotinterventionen auf andere Standorte oder ganze Systeme zu übertragen und sie so einer Vielzahl von Menschen zugänglich zu machen. Dieser Beitrag möchte für den deutschsprachigen Raum auf Basis einer Literatur-Review einen ersten Überblick über einige theoretische Scaling-Up-Modelle sowie praktische Leitlinien für ein erfolgreiches Scaling-Up geben. Der Blick in die aktuelle Forschung liefert wichtige Erkenntnisse zur Definition von Scaling-Up und von damit verbundenen Konzepten, den verschiedenen Typen von Scaling-Up, zu zentralen Akteuren und ihren spezifischen Rollen, zum Ablauf von Scaling-Up-Prozessen sowie zu begünstigenden und hinderlichen Kontextfaktoren für erfolgreiches Scaling-Up. Damit kann dieser Artikel einerseits die Planung und praktische Umsetzung konkreter Scaling-Up-Vorhaben unterstützen und andererseits Anregungen für die weitere Forschung auf diesem Gebiet bieten.<br
Keywords: Gesundheitsförderung; Scaling-Up; Nachhaltigkeit; Implementierung; Literaturübersicht

Scientific Cooperation and the Co-production of Scientific Outcomes for Physical Activity Promotion: Results From a Transdisciplinary Research Consortium - Ferschl, Susanne; Till, Maike; Abu-Omar, Karim; Pfeifer, Klaus; Gelius, Peter (Frontiers in Public Health, 2021)
Background: To tackle complex societal challenges such as the high prevalence of physical inactivity, research funding is increasingly channeled toward cross-disciplinary research consortia. This study focused on exchange and cooperation (E&C) among the scientists of a 5-year transdisciplinary research initiative in Germany. Researchers' perceptions of E&C were combined with numbers of collaborative products during the project's life to make the developments of E&C and the quality of collaborative products visible. Methods: We applied a mixed-methods design including a qualitative content analysis of pre-interviews, focus-group interviews, and documents as well as a quantitative analysis of research (scientific publications, books, conference participations) and training outcomes (supervised bachelor's, master's, and Ph.D. theses). Inductive and deductive approaches were combined to analyze factors of collaborative readiness and to identify perceptions of E&C among project teams. Based on Hall et al.'s “Conceptual Model for Evaluation of Collaborative Initiatives,” the project period was separated into phases of “collaborative readiness,” “collaborative capacity,” and “collaborative products.” Results: Our findings revealed a discrepancy between the objectively assessed concepts of collaborative readiness and researchers' reported perceptions of E&C during the early project stage. A set of E&C hindering factors identified during the initial project phase remained present until the final project stage. Further, E&C among scientists increased over time, as reflected by researchers' perceptions. Reports of scientists also showed that outcomes were co-produced at the final project stage for the first time, while knowledge integration had not yet been achieved. Generally, the number of collaborative products (particularly scientific publications) also substantially increased over time. E&C was supported and promoted by the efforts of the coordinating sub-project. Conclusion: Scientific E&C is a learning process and needs time to develop. A participatory research approach taking into account the perspectives on and requirements for E&C during the project's design might lay the ground for suitable, supportive, and transparent conditions for effective and successful E&C. Despite their time- and resource-consuming nature, cross-disciplinary research initiatives provide a fertile context in which to generate new solutions for pressing societal issues given that long-term funding and the establishment of an overarching coordination organ is assure
Keywords: cooperation of science teams; The Science of Team Science; transdisciplinary research consortium; physical activity promotion; collaborative readiness; collaborative products

Sociodemographic correlates of physical activity and sport among adults in Germany: 1997–2018 - Abu-Omar, Karim; Messing, Sven; Sarshar, Mustafa; Gelius, Peter; Ferschl, Susanne; Finger, Jonas; Bauman, Adrian (German Journal of Exercise and Sport Research, 2021)
Introduction Promoting physical activity (PA) is a key strategy to prevent noncommunicable diseases worldwide. In order to monitor physical activity levels in Germany, several large-scale studies have reported on prevalence rates and correlates. However, a comprehensive analysis of correlates of PA over time is currently lacking for Germany. Methods For the analysis, 13 national cross-sectional data sets were utilized. Data analysis was restricted to respondents aged 18 and older. In a first step, data sets were kept separate in order to explore social gradients of PA and sport. In the second step, data sets were pooled, demographic factors harmonized and binary logistic regressions were conducted. Results Regarding sports participation, different data sets indicate comparable social gradients. People with a higher age, lower income, lower levels of education, or a migrant background consistently have a higher risk of not engaging in sports. Compared to sports participation, social gradients are less pronounced for engaging in vigorous PA. Higher age, lower education, and lower income are also markers for an increased risk of not engaging in vigorous PA. Discussion The study confirms that factors of age, income, education and migrant background continue to contribute to differentials in sport and vigorous PA participation in Germany. For policy-making, this implies that PA promotion should focus on systems-based actions that might reduce population-wide inequalities. Future research might focus on pooling single studies with smaller samples in order to investigate PA and sports participation in specific disadvantaged target groups.<br
Keywords: Social gradients; Vigorous physical activity; Sport participation; Pooled data analysis; Correlates over time

The Factbook on the Illicit Trade in Tobacco Products 5 – Germany - Calderoni, Francesco; De Simoni, Marco; Favarin, Serena; Lehmann, Susanne (2013)

The winner takes it all? Characteristics of adolescent at-risk/problem gamblers in Switzerland. - Lehmann, Susanne; Akre, Christina; Berchtold, Andre; Flatz, Aline; Suris, Joan-Carles (International Journal of Adolescent Medicine and Health, 2016)
Gambling has and still entertains people in almost all societies throughout the world. Western societies have faced considerable changes in the amount and accessibility of gambling possibilities during the last decades, and the rates of both adolescent gamblers and problem gamblers have increased significantly. To determine the characteristics of at-risk and problem adolescent gamblers in Switzerland. The study population consisted of 3134 students (1669 females) attending post-mandatory education in 15 randomly chosen centres. Participants were divided into non- (n=2207), non-problematic (n=754) and at-risk/ problematic gamblers (n=176). Both gambling groups were compared to non-gamblers on socio-demographic measures, substance use and Internet use. Overall, 29.6% had gambled during the past year and 5.6% had gambled in a risky or problematic way. Compared to non-gamblers and after controlling for potential confounders, non-problem gamblers were significantly more likely to be male, apprentices and to misuse alcohol. At-risk/problematic gamblers were additionally more likely to smoke cannabis, to be problematic Internet users and to be non-Swiss than non-gamblers. At-risk and problematic adolescent gambling is associated with other health risk behaviours. Health practitioners should include gambling in the psycho-social screening and preventive counselling of adolescents. BACKGROUND OBJECTIVE SUBJECTS METHODS CONCLUSION

What difference does it make to be health literate? Probing into the associations between health literacy scores and health behaviors. (Unpublished) - Lehmann, Susanne; Abel, Thomas (Dreiländerkongress "Bildung und Gesundheit"., 2016)